Perbedaan Budaya dan Adaptasi Antarbudaya dalam Relasi Kemitraan Inti-Plasma - Sri Rejeki, MC Ninik (Jurnal ILMU KOMUNIKASI, 2007)
Abstract: The difference of culture is a primary characteristic of the intercultural communication. Cultural difference implies to the different communication behavior. These differences raise various communication problems in which its solution needs certain communication competence. Cultural difference in estate system in Indonesia was started by dualistic economy reality and it turns to the raise of the cultural dualism. In one side big estate is oriented to modern capitalism (nucleus estate), and another side small holders (plasma farmer) is oriented to the traditional pre-capitalism. They develop intercultural communication competence by establishing strategy of convergent and divergent adaptation. The difference between nucleus estate and plasma farmer is based on the differences of existence in the orientation of farming and structural tightness. The communities of nucleus estate have culture that take root in economic interests (commercial). Meanwhile some of farmer communities are oriented to family and the communities’ interest. Standardization of existence and control towards job is a part of structural tightness characteristic and nucleus estate’s masculinity. However there are a few modern farmers that begin to concern to the business. This study also shows the adaptation strategy in the communication behavior is applied by nucleus estate people. Adaptation strategy is divided into two strategies: (1) convergent strategy manifested by the adjustment in other party’s communication behavior, meanwhile the divergent strategy manifested by the show of the different behavior appearance as their culture identity.